Sistem Informasi Pencetakan Kartu Peserta Ujian di SMA Negeri 6 Kota Bengkulu - nadiza lediwara; Suhar totok; Yosi Herianti (Universitas PGRI Yogyakarta, 2021)
Examination is a process carried out by the teacher to measure and determine the achievement of student competencies on learning process. Before the exam is conducted, the administrative staff has prepared an identification for each students, namely the presence of a school exam participant card. Students can get a school exam participant card on the condition that they have completed all payments related to the school treasurer. In SMA 6 Negeri Kota Bengkulu, the processing of student data and making the test participant cards still used Microsoft Excel for inputting data and making school exam cards. The data processing system has not used software equipped with a database or a program that creates a document. Therefore, it is necessary to design and create web platform Information System for Printing Test Participant Cards at SMA Negeri 6 Kota Bengkulu using the PHP programming language and the MYSQL database.